Reduced magnetisation transfer ratio in cognitively impaired patients at the very early stage of multiple sclerosis: a prospective, multicenter, cross-sectional study. Issue 4 (10th April 2014) - Faiss, J H; Dähne, D; Baum, K; Deppe, R; Hoffmann, F; Köhler, W; Kunkel, A; Lux, A; Matzke, M; Penner, I K; Sailer, M; Zettl, U K
Abstract : Objectives: Cognitive impairment belongs to the core symptoms in multiple sclerosis (MS) and can already be present at the very early stages of the disease. The present study evaluated cognitive functioning after the first clinical presentation suggestive of MS and brain tissue damage in a non-lesion focused MRI approach by using magnetisation transfer imaging (MTI). Setting and participants: 47 patients (15 men and 32 women; mean age: 31.17 years) after the first clinical event suggestive of MS were recruited in six different MS centres in Germany and underwent a neuropsychological test battery including tests for attention, memory and executive function as well as depression and fatigue. MTI and conventional MRI measures (T1/T2 lesion load) were assessed. In addition, Magnetisation Transfer Ratio (MTR) maps were calculated. Primary outcome measure was the investigation of cognitive dysfunction in very early MS in correlation to MRI data. Results: 55.3% of patients with MS failed at least one test parameter. Specifically, 6% were reduced in working memory, 14.9% in focused attention, 25.5% in figural learning and up to 14.9% in executive function. When the sample was subdivided into cognitively impaired and preserved, MTR scores within the cognitively impaired subgroup were significantly lower compared with the preserved group (t(43)=2.346, p=0.02*). No significant differences between the two groups were found in T2-weighted and T1-weighted lesion volume. Conclusions: After the first MS-related clinical event, 55.3% of patients showed distinct cognitive deficits. Cognitively impaired patients had significantly lower whole brain MTR, but no differences in focal brain lesion volumes supporting the idea that early cognitive deficits may be related to diffuse loss of brain tissue integrity.